Hadhrami Network And Neo-Sufism In Bolaang Mongondow - Almunauwar Bin Rusli (AIUA Journal of Islamic Education, 2019)
This article discusses the Hadhrami network and neo-sufism in East Bolaang Mongondow, North Sulawesi as the largest Muslim ethnic group (57,109 people). The problem with their existence is that there is no information of history and power since the fall of the New Order. This article employs qualitative-explanation research with sociological approach. Participatory observations, in-depth interviews and documentary studies were conducted at Nuangan and Kotamobagu. The result of research show that the Hadhrami network was formed from the 19th century by two figures, Sayyid Husein bin Saleh bin Jindan and Sayyid Salim bin Saleh bin Jindan. They could survive because of the interaction, contextualization, indigenization and vernacularization of Islamic values. On the other hand, this network creates of neo-sufism practiced in the Majelis Ittihadul Ummah Muhammad SAW (Habib Umar Bin Salim Assegaf) and the Majelis Nurul Khairaat (Habib Abdurrahman Bin Jindan) with Thariqah Alawiyyah. It concludes that the descendants of Hadhrami in East Bolaang Mongondow made the mosque, school, and market as the three main ways to promote moderation and preventing conflict in socio-religious life.